(untitled) (Revista Crioula, 2022)
Analysis of Torto arado (2019), by Itamar Vieira Junior with attention to the point of view of narration, since the narrators of the novel, three quilombola women, reveal in the work the marks left by slavery in Brazil, which consequently helps in the understanding of structural and institutional racism in Brazilian society. As a result, it appears that the novel expresses the relationship between the slavery past and the current portrait of blacks, quilombola communities and social inequality in Brazil.